Asset securitisation as a strategic tool: Its influence on the mortgage and credit card market, and the likely impact on its development of proposed changes to international accounting standards and regulatory capital guidelines. - Smith, Andrew Michael Donald (2005)
The use of securitisation as a strategic tool has grown quickly over the last thirty five years. From its development in the US mortgage market in the 1970's it is now seen as a mainstream funding tool by many organisations and has been used to finance assets as diverse as mortgages, rock album sales and football grounds. Specific examples of organisations that have used securitisation to grow their business are looked at in detail. The industry is also now facing challenges from changes to global accounting and regulatory capital guidelines and these have the potential to change the way in which it is used in the future.